Salmonella enterica serotype typhimurium and S. Stanley differ in genomic evolutionary patterns and early immune responses in human THP-1 cell line and CD14+ monocytes. (April 2019) - Huang, Chin-Chin; Wang, Shao-Hung; Chin, Li-Te; Huang, Chang-Lin; Sun, Li-Ting; Chiou, Chien-Shun; Tu, Pei-Chun; Chu, Chishih
Highlights: Salmonella Typhimurium and S. Stanley are two most prevalent serogroup B serogroup to infect human, but differ in prevalence. Genetically diverse S . Typhimurium and clonally disseminated S. Stanley differed in immune response with higher phagocytized number, lower intracellular survival, higher ROS production and higher inflammation cytokine IL-1β expression by dead bacteria for S. Stanley, that may lead low prevalence of S . Stanley. Abstract: Salmonella Typhimurium and S. Stanley are the most prevalent serogroup B serovars to infect humans in Taiwan. The aim was to determine possible factors to influence the prevalence between S. Typhimurium and S. Stanley. Genotypes were determined by pulsed field gel electrophoresis (PFGE) analysis and the intracellular survival, phagocytosis, reactive oxygen species (ROS) production of human monocyte THP-1 cell and tumor necrosis factor-α(TNF-α), interleukin-6 (IL-6), and IL-1βexpression in peripheral blood CD14 + cells after infection were analyzed. 182 S. Stanley was clonal disseminated with main pulsotypes 2 from 2004 to 2007. Overall S. Typhimurium evolved more genotypes, while S. Stanley conserved in genotypes. Human blood CD14 + monocytes expressed TNF-α, IL-6 and IL-1β differently among serovars and bacterial conditions (live vs. killed). Live S. Stanley and S . Typhimurium suppressed the TNF-α and IL-6 expression compared to killed bacteria. However, live S . Typhimurium stimulated more IL-1β expression than the killed bacteria, but S . Stanley expressed similar IL-1β levels in both conditions. Furthermore, S . Stanley and S . Typhimurium differed in intracellular survival in the THP-1 cells, an early decrease for S. Stanley, not for S . Typhimurium. Additionally, higher reactive oxygen species (ROS) production in THP-1 cells was found agsinst S. Stanley infection, not found in S . Typhimurium. However, some isolates of S. Stanley could recover from early loss to become more in the monocytes than S. Typhimurium. Difference in phagocytized number, intracellular survival, ROS production and IL-1β expression may contribute to prevalence different between two serovars.